BUREAUCRATIC REFORM IN AN EFFORT TO STRENGTHEN LOCAL GOVERNMENT FUNCTIONS - Muhadam Labolo (Sean Institute, 2022)
The bureaucratic reform strategy is an effort and step to strengthen the function of local government and to respond to challenges in the globalization era. Bureaucratic reform not only simplifies the bureaucratic structure but changes the mindset and work culture in the bureaucracy, especially in the administrative management of local governments. Regions that are successful with bureaucratic reform usually have regional heads with strong political commitment, adequate knowledge and competence in bureaucratic reform, as well as experience. The main objective of this study is to analyze the role of bureaucratic reform in strengthening local government functions. This research will use a qualitative approach with descriptive methods. Research results show that challenges such as overlapping regulations, lack of budget, lack of political awareness, and low knowledge of local government functions can hinder the performance and effectiveness of local governments in carrying out their duties and responsibilities. Forms of bureaucratic reform that can be carried out include simplification and harmonization of regulations, increasing local revenue, improving the quality of bureaucratic human resources, and strengthening community participation.